RESULTS OF MULTICOMPONENT ANALYSIS OF PRODUCED WATER, SELECTED WELL № 12 OF THE MINGBULAK FIELD (American Journal of Technology and Applied Sciences, 2024)
The main purpose of the water supply system while maintaining reservoir pressure is to extract the required amount of water suitable for injection into the reservoir, distribute it between injection wells and pump it into the reservoir.